Autoantibodies to CD59, CD55, CD46 or CD35 are not associated with atypical haemolytic uraemic syndrome (aHUS). Issue 2 (February 2015) - Watson, Rachael; Wearmouth, Emma; McLoughlin, Amy-Claire; Jackson, Arthur; Ward, Sophie; Bertram, Paula; Bennaceur, Karim; Barker, Catriona E.; Pappworth, Isabel Y.; Kavanagh, David; Lea, Susan M.; Atkinson, John P.; et al.
Highlights First report of analysis of aHUS patients for autoantibodies to CD46, CD55, CD35 and CD59. Surprisingly no aAb to surface bound complement regulators found in association with aHUS. Surface regulators could be protected from mechanisms of autoantibody formation in aHUS.